Potential role of odontoblasts in the innate immune response of the dental pulp - Tetiana Haniastuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: Odontoblasts are the cells lining of tooth’s hard structure at the dentin-pulp border, which become the first cells encountered oral microorganisms entering dentin. However, they do not only form a physical barrier by producing dentin, but also provide an innate immune barrier for the tooth. Purpose: The aim of this review was to discuss the potential role of odontoblasts in the innate immune response of the dental pulp. Reviews: Recent studies have proven that odontoblasts express toll-like receptors, and capable of producing chemokines (i.e. IL-8, CCL2, CXCL2, and CXCL10), and cytokines (IL-1β and TNF-α) following lipopolysacharide exposure. Thereby odontoblasts are actively participating in the recruitment of immune cells in response to caries–derived bacterial products. Furthermore, odontoblasts also produce antimicrobial peptides (hBD-1, hBD-2, and hBD-3), and transform growth factor β that induce antimicrobial and anti-inflammatory activities. Conclusion: The presence of those innate immune molecules indicates that the nonspecific, natural, and rapidly acting defense may also be an important function of odontoblasts.